Plea bargain: psychological and legal aspects (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The issue regarding the concept of plea bargain will be analyzed from two perspectives: psychological and legal. In relation to the first perspective, the concept of plea bargain will be analyzed through behaviorism, social-historical and psychoanalysis. For the second aspect, will be verified the main legal rules which regulate the plea bargain in Brazil.
Keywords: plea bargain; plea agreement; psychological aspects; legal aspects; criminal investigation